Food and Agriculture Organisation background: India’s success - Khadka, Shyam (Indian Farming, 2018)
There is a high level of inter dependence among each priority area and the results of one priority area requires inputs from other priority areas. Cross cutting issues such as policy and governance, capacity building, gender, data and information sharing will be addressed as integral parts for each of the priority areas. FAO will use its comparative advantage as a specialized agency of the United Nations and use the knowledge it has gained over the years in designing and implementing programmes in India.